Translation and adaptation studies on common ground: the Murat Davman crime fiction series - Karabulut, Emine; Karadag, Ayse Banu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
When claims emerged that & Uuml;mit Deniz's Murat Davman crime fiction series (1956-1974) was an adaptation of Mickey Spillane's Mike Hammer series (1946-1996), they were quickly debunked. The claims, however, prompted questions about whether Deniz' series may be an adaptation of other novels Deniz translated into Turkish. This article reads Deniz' corpus with the tools of intertextuality and translation theory and characterizes his series as both a concealed translation/global adaptation of the Hammer series, other novels and an original work. In so doing, it brings together hitherto distinct disciplines and offers a revised constructive interpretation of the East-West relationship when it comes to discussion of the circulation of texts, which is usually structured by assumptions of the incompetency and backwardness of the East and the perceived superiority of the West. Through the series, we see the importance of recognizing the potential of East-West as moments of mutual enrichment.
Keywords: Crime fiction; Turkish literature; adaptation; intertextuality; translation studies; Literature